Fragilidade em idosos comunitários: um estudo de coorte - Mariana Asmar Alencar (2012)
Frailty is characterized as a state of increased vulnerability resulting from decreased physiological reserves, multi-system dysregulation and limited capacity to maintain homeostasis. It is generally associated with a greater risk of fall, cognitive and functional decline, nursing home admission, hospitalization, and death. However, despite the association between frailty and adverse outcomes, frailty seems not to be an irreversible process and is certainly not an inevitable trajectory to death. Therefore, a better understanding of the relationship between frailty and longitudinal changes is of considerable interest for clinical assistance and public health, once it can help in adoption of interventions that result in an improvement of elderly health care. The aim of the present study was to assess frailty of community-dwelling elderly and identify transition between states and the risk of adverse outcome over a 12-month. This study was a cohort with two waves of interviews, one at baseline and other after 12 months. A random sample, with 207 community-dwelling elderly individuals aged 65 years or older with or without cognitive impairment, assisted in Jenny Faria Institute of elderly health care of the Federal University of Minas Gerais General Hospital was used. Were assessed socio-demographic characteristics, frailty, cognitive function, nutritional status, medical conditions, physical function and the occurrence, over 12 months, of adverse outcomes such as fall, cognitive decline, stay at home in bed, hospitalization and death. Frailty was assessed using the criteria developed by Fried and colleagues, in which frailty was defined as having weight loss, exhaustion, low activity level, weakness and gait slowness. Participants meeting three or more criteria were classified as frail; those meeting one or two criteria were classified as pre-frail and those meeting none were considered non-frail. Descriptive, univariate and multivariate analysis was used. The level of significance was set to 0.05. Among the 207 participants evaluated at baseline, 47 (22.7%) were non-frail, 112 (54.1%) pre-frail and 48 (23.2%) frail. Frail elderly were older, had a lower level of education, lower body mass index, lower score of Mini Mental State Examination (MMSE) and performed less instrumental activities of daily living and advanced activities of daily living (AADL) when compared to pre-frail or non-frail. Besides, frail elderly had more frequency of cognitive impairment, positive screening for depression, sleep problems, loss of appetite and dependence on basic activities of daily living. During this cohort, 88% (n=182) of elderly individual completed the follow up, 5.8% (n=12) died and 6.2% (n=13) were lost to follow up. Among the total of reevaluated elderly, 36.8% (n=67) of the participants made transitions between states of frailty in the 12-month period, which occurred in both directions of worsening frailty (24.2%; n=44) and of improving (12.6%; n=23) frailty status. The variables identified as predictors of worsened frailty over the 12-month period were history of cancer, urinary incontinence and reductions on capacity of performing AADL. Frail elderly at baseline were with a 5-fold greater risk of die or decrease cognitive function (MMSE score decline), 3-fold greater risk of staying at home in bed and 2-fold greater risk of hospitalization or fallen than those who were non-frail or pre-frail over 12 month period. In conclusion, the present cohort study verifies that even within a short period of time (12 months) frailty is a dynamic process with transitions in both directions (worsening and improvement) and place elderly people in an increased risk of adverse outcomes. Therefore, the development and evaluation of interventions designed to prevent or ameliorate frailty should remain one the top priorities in frailty research.